Patient-Specific 3D Printed Models of Aortic aneurysm and aortic dissection - Sun, Zhonghua; Squelch, A. (American Scientific Publishers, 2017)
The purpose of this study is to investigate the accuracy of 3D printed models in demonstrating aortic aneurysm and dissection. Three patients with type B aortic dissection in 2 cases and aortic aneurysm involving the aortic arch in 1 case were selected with high resolution CT angiographic images used for generation of patient-specific 3D printed models. Measurements of maximal diameters at different anatomical locations were performed and compared between pre-3D printing CT images, 3D printed models and post-3D printing CT images. An excellent agreement was found between these measurements with no significant differences (p = 0.96 – 0.98). The differences between these measurements were less than 0.8 mm, indicating the high accuracy of the 3D printed models for replicating the aortic structures and pathologies. 3D virtual intravascular endoscopy was successfully generated in these images showing similar intravascular changes. Patient-specific 3D printed models represent a promising technique for studying cardiovascular disease.